Aroma Components of Vitis vinifera L. cv. Chenin blanc Grapes and Their Changes During Maturation - Augustyn, 0. P. H.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
Samples of Chenin blanc grapes from 3 localities and at various stages of maturity were harvested over a period of 11 weeks. The freon extracted aroma components were subjected to gas chromatographic and coupled gas chromatographic-mass spectrometric analyses. No measureable amounts ofterpenoid components were detected in any of the samples. Two isomers of 2,4-decadienal, a novel component in Vitis vinifera L. cultivars, occurred in relatively large concentrations in all samples. Origin of sample and degree of maturity have an insignificant effect on the concentration of selected aroma components.